Fatores condicionantes da utilização da Internet na compra de serviços de viagens e turismo: estudo com turistas brasileiros em visita à Natal-RN - Guardia, Mabel Simone de Araújo Bezerra (2006)
In today s global society, companies have become even more competitive with the abundance of information that prospective clients have available to them. This way the tourist services has appropriate the distribution using electronics ways as information for doing acquirement services. This work, shows the adopted provision of on-line tourist services does have suited apportionment for factors and buy decisions. The method used is a survey applied to the tourists, at international airport Augusto Severo, no matter why the visit reason to Natal city, at all, they were 210 people, being the chief variables evaluated the tourist perception of facility, utility, benefits, amenity and pleasure from the Internet s use, under the terms at the tourists experiences from the WEB about to acquisitions and researches. The results acquaint that the younger tourists or less experts tourists, in visit to Natal, demonstrated greater bias to the Internet s use than the other people. By the way women have a larger representation as a consumer from the WEB and finally, people along greater study tends to adopt. The work s contribution provides greater knowledge for the tourism executives about how might use the Internet, as well as bring forward a scene propitious for the on-line diffuseness service